Oil Revenues and Inflation Dynamics in Iraq: Evidence from ARDL Approach - Rizgar Ali Hameed; Mamon Adam Maarof; Akram Salih Yousif (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study examines the relationship between oil revenues and inflation dynamics in Iraq, a rentier economy highly dependent on oil as its primary source of public finance. Given the limitations of conventional inflation measures, the study adopts the GDP deflator as a more comprehensive indicator of price changes across the economy. The main objective is to analyze both the short-run and long-run effects of oil revenues and selected macroeconomic variables on the GDP deflator over the period 2004–2022. The study employs the Autoregressive Distributed Lag (ARDL) approach, which is suitable for small sample sizes and allows for the estimation of dynamic relationships among variables with mixed orders of integration. The findings reveal that broad money supply significantly influences the GDP deflator in the short run, while oil revenues exert a positive and statistically significant effect in the long run, confirming their dominant role in driving inflation. In contrast, variables such as the exchange rate, government expenditure, and tax revenues do not show significant long-term effects. These results indicate that inflation in Iraq is primarily demand-driven through oil revenue channels, reflecting structural dependence on the oil sector. The study concludes that effective management of oil revenues, alongside coordinated fiscal and monetary policies and economic diversification, is essential to achieving price stability and sustainable economic growth in oil-dependent economies.